2010
DOI: 10.1007/s00027-010-0145-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental factors and predation on benthic communities in headwater streams

Abstract: Structure and composition of benthic macroinvertebrate assemblages were investigated during three consecutive years in six headwater streams that exhibit a high variation in environmental conditions, habitat structure and predatory pressure. We examined whether the abundance of functional feeding groups could be best predicted by the abundance of predators and some habitat and chemical variables. Mean density and biomass of macroinvertebrate functional feeding groups varied significantly throughout the study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 68 publications
(69 reference statements)
2
20
0
Order By: Relevance
“…Multiple authors provide different answers, and in the opinion of many of them, it mostly depends on the type of reservoir. For example, Nicola et al (2010) claimed that in streams, benthic communities are most affected by water chemistry, and less by fish predation. On the other hand, Williams and Taylor (2003) found a significant influence of fish predations on the density and taxonomic structure of invertebrates in isolated pools of an intermittent stream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple authors provide different answers, and in the opinion of many of them, it mostly depends on the type of reservoir. For example, Nicola et al (2010) claimed that in streams, benthic communities are most affected by water chemistry, and less by fish predation. On the other hand, Williams and Taylor (2003) found a significant influence of fish predations on the density and taxonomic structure of invertebrates in isolated pools of an intermittent stream.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Choe et al (2014) showed that in the examined regulated watercourse, predatory fish can be the main limiting factor for certain groups of invertebrates. On the other hand, Nicola et al (2010) found that the structures of benthic macroinvertebrates are shaped primarily by water chemism, rather than by the presence of predatory fish. The aim of our study was to determine the impact on the structures of macrozoobenthos in a small field watercourse exerted by abiotic conditions, with the concurrent lack of fish and varied intensity of anthropopressure.…”
Section: Introductionmentioning
confidence: 99%
“…The canonical correlation analysis showed the influence of water chemistry on the macroinvertebrate community, as aquatic chemistry variables are frequently used to explain variation in benthic communities (Nicola et al 2010). Alkalinity, pH and Dissolved Oxygen were shown as the most important environmental factors, as they were associated to the decomposition of organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to understand the relative roles of habitat and water chemistry in structuring macroinvertebrate communities in headwaters (Nicola et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation